2010, No. 6, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Birutė Visokavičienė, The role of the monetary policy during the global financial crisis (2008-2009), 7Valerija Gerikienė, Ramunė Kugaudaitė, Problems of the application of theoretical wage models, 19Rusak Olga Arkadievna, The accounting aspects of the insurance transactions problem, 40Kristina Rudžionienė, Aušra Morkevičienė, The conservatism principle in accounting: case of Lithuania, 50Giedrė Laurinavičienė, Comparative analysis of income statements formed according to 1st IAS „Presentation of financial statements“, 3rd BAS „Income statement“ and the Fourth directive, 60Jolita Jarmalaitė, Comparative analysis of inventory accounting following 2nd IAS „Inventories“ and 9th BAS „Inventories“, 71Vaclovas Lakis, Giedrė Damaševičiūtė, The factors affecting relationships of internal auditors and auditees , 82Vladislav Tomaševič, Efficiency analysis and evaluation of investment projects, 95Nijolė Pakalnienė, Sufficiency of professional competence of graduates of Utena college accounting program for practical activity, 105Jonas Mackevičius, Company internal control system: original researches,  new thoughts, 114
Keywords: none